Secreted Spitz triggers the DER signaling pathway and is a limiting component in embryonic ventral ectoderm determination. - Schweitzer, R.; Shaharabany, M.; Seger, R.; Shilo, B.Z. (Genes & Development, 1995)
The spitz gene encoding a TGF-alpha homolog, has been shown to affect a subset of developmental processes that are similar to those regulated by DER, the Drosophila EGF receptor homolog. This work demonstrates that Spitz triggers the DER signaling cascade. Addition of a secreted, but not the membrane-associated form of Spitz to S2 Drosophila cells expressing DER gives rise to a rapid tyrosine autophosphorylation of DER. Following autophosphorylation, DER associates with the Drk adapter protein. Consequently, activation of MAP kinase is observed. The profile of MAP kinase activation provides a quantitative assay for DER activation. A dose response between the levels of Spitz and MAP kinase activity was observed. The secreted Spitz protein was expressed in embryos to assess its biological activity. An alteration in cell fates was observed in the ventral ectoderm, such that lateral cells acquired the ventral-most fates. The result indicates that graded activation of the DER pathway may normally give rise to a repertoire of discrete cell fates in the ventral ectoderm. Spatially restricted processing of Spitz may be responsible for this graded activation. The Rhomboid (Rho) and Star proteins were suggested, on the basis of genetic interactions, to act as modulators of DER signaling. No alteration in DER autophosphorylation or the pattern of MAP kinase activation by secreted Spitz was observed when the Rho and Star proteins were coexpressed with DER in S2 cells. In embryos mutant for rho or Star the ventralizing effect of secreted Spitz is epistatic, suggesting that Rho and Star may normally facilitate processing of the Spitz precursor.